1987
DOI: 10.1161/01.cir.75.4.756
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of mitral annular shape to the diagnosis of mitral valve prolapse.

Abstract: The geometric or anatomic diagnosis of mitral valve prolapse, as opposed to the pathologic diagnosis of myxomatous valve disease, is based on the relationship of the mitral leaflets to the surrounding anulus. Current echocardiographic criteria for this diagnosis include leaflet displacement above the annular hinge points in any two-dimensional view; implicit in this equivalent use of intersecting views is the assumption that the mitral anulus is a euclidean plane. Prolapse by these criteria is found in a surpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
145
0
7

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 316 publications
(154 citation statements)
references
References 44 publications
1
145
0
7
Order By: Relevance
“…According to Levine et al (1987), Salgo et al (2002), Votta et al (2008) and Mahmood et al (2010), the mitral annulus is flat during diastole and becomes saddle shaped only during systole. In particular, Salgo et al (2002) and Votta et al (2008) found that the annulus non-planarity mainly affects the mobility of the posterior leaflet and facilitates the valve closure.…”
Section: Closing Remarksmentioning
confidence: 99%
“…According to Levine et al (1987), Salgo et al (2002), Votta et al (2008) and Mahmood et al (2010), the mitral annulus is flat during diastole and becomes saddle shaped only during systole. In particular, Salgo et al (2002) and Votta et al (2008) found that the annulus non-planarity mainly affects the mobility of the posterior leaflet and facilitates the valve closure.…”
Section: Closing Remarksmentioning
confidence: 99%
“…Therefore, in principle, it is possible for the leaflets to lie above the annular insertion points in mediolateral imaging planes through the low points of the annulus (implying prolapse by current criteria),16"17 and to lie below the annular insertions in anteroposterior imaging planes through the high points (implying normality). 13 Clinical studies indicate that this may be the case. There is a higher prevalence of superior leallet displacement in a mediolateral plane (the apical four-chamber view) than in an anteroposterior plane (the parasternal long-axis view), 16"1720-22 particularly in otherwise normal individuals.5 Also, patients with leaflet displacement above the low points but not the high points of the annulus are similar to normal individuals, that is, free of the disease prolapse.…”
mentioning
confidence: 99%
“…Images were recorded on a CD, including complete parasternal, apical and subscostal views, and colour Doppler assessment of the valvular regurgitation. We measured the displacement of the anterior and posterior mitral leaflets in the parasternal and apical long axis views, scanned by tilting the transducer to visualize all the three scallops of the posterior leaflets [8,9,12]. The thickness of the mitral leaflets during diastasis was measured from the leading to the trailing edge of the thickest area of the mid-portion of the leaflet, excluding focal areas of thickness and the chordae [13,14].…”
Section: Echocardiographic Methodsmentioning
confidence: 99%
“…Echocardiographic MVP has been found in 50% of patients with PSP C o p y r ig h t G e n e r a l P r a c t ic e A ir w a y s G r o u p R e p r o d u c t io n p r o h ib it e d [7]. Studies describing the three-dimensional shape of the mitral annulus [8,9] have allowed the two-dimensional (2D-) echocardiographic characterization of the prolapse to be refined, thus minimizing false positive diagnoses [10,11]. We used current 2D-echocardiographic criteria to determine the prevalence of MVP in patients with PSP admitted to Adan teaching hospital in the Ahmadi Governorate in Kuwait.…”
Section: Introductionmentioning
confidence: 99%